Experiencing natural environments, experiencing health : a health psychology perspective : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Health Psychology, Massey University, Albany, New Zealand - Malur, Malini (Massey University, 2010)
This aim of this study was to explore the importance of natural surroundings to human health from a health psychology perspective. The increase in built environments have replaced green spaces in the urban areas and the effects of this has been explored by several disciplines ranging from environmental psychology, leisure studies, urban planning, public health to name a few. Findings from these studies have shown that natural environments do play a significant role in human health. However, it was deemed that exploring the influence of nature on human health from a health psychology viewpoint would provide a different dimension to this established link between nature and humans to press for preserving and providing more green spaces in the cities. Urban green areas offer several benefits such as space for exercise, leisure, psychological space for rejuvenating, healing and social connections that are all crucial for our wellbeing. This study explores the many ways natural settings contribute to health and well-being from a health psychology angle. A qualitative design was employed using a phenomenological approach to understand the everyday experience of being in nature/natural environments. Cornwall Park/One Tree Hill in Auckland was chosen as the site for this study. Nine women and men between the ages of 30 and 70 were chosen from this site to take part in the study. Methods of data collection were mainly in-depth interviews and photo-discussion. The data was analysed using a phenomenological approach based on the guidelines developed by Moustakas (1994) and van Manen (1990). The findings revealed that natural surroundings influenced people positively in many ways that contributed to their physical, mental and spiritual well-being. Natural environments satisfied a wide-range of needs, such as providing a place/space to exercise, to be alone and reflect, connect with nature, recreate, heal and socialise to name a few, in green, quiet, pollution-free, aesthetically pleasing settings. The essence of the phenomenon that is estimated to have been captured in the study is, “human experience in nature from the point of view of health psychology, or human experience of wellness, being in nature”.
Keywords: Health psychology; Environmental psychology; Wellness; Wellbeing; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology